Association of splenic MR elastographic findings with gastroesophageal varices in patients with chronic liver disease. Issue 1 (14th November 2013) - Morisaka, Hiroyuki; Motosugi, Utaroh; Ichikawa, Shintaro; Sano, Katsuhiro; Ichikawa, Tomoaki; Enomoto, Nobuyuki
<x xml:space="preserve">Abstract</x> Purpose To identify magnetic resonance imaging (MRI)‐based parameters associated with gastroesophageal varices (GEVs) in patients with chronic liver disease. Materials and Methods Ninety‐three patients were divided into three groups based on endoscopic findings: group 1 with no GEVs (n = 49), group 2 with mild GEVs (n = 30), and group 3 with severe GEVs (n = 14). We used a multivariate logistic regression analysis to assess liver stiffness, aspartate aminotransferase‐to‐platelet ratio index, spleen stiffness and volume, portal vein velocity, cross‐sectional area, and flow volumes potential independent associators of any (mild and severe) GEVs or severe GEVs. Results The analysis showed that spleen and liver stiffness and spleen volume were independently associated with any GEVs (spleen stiffness, odds ratio [95% confidence interval], 1.25 [1.04–1.68], P = 0.018; liver stiffness, 1.52 [1.13–2.17], P = 0.006; spleen volume, 1.01 [1.00–1.01], P = 0.016), whereas spleen stiffness was associated with severe GEVs (1.82 [1.25–2.95]; P = 0.005). Conclusion: Liver and spleen stiffness and spleen volume are associated with GEVs in patients with chronic liver disease. Compared with liver stiffness and spleen volume, spleen stiffness is more strongly associated with severe GEVs. J. Magn. Reson. Imaging 2015;41:117–124. © 2013 Wiley Periodicals, Inc.